Prison In Islamic Criminal Law Perspective - Abdul Balgis Hi Talib (Peneliti.net, 2021)
Prison as one of the security systems which is part of the criminal system in Indonesia has become something that is prima donna in imposing sanctions on criminals. The implementation of prisons in Indonesia is regulated in Law Number 15 of 1995 concerning correctional facilities, as the name implies, this law regulates the implementation of prisons with a prison system which is a long process from the image of colonial-era prisons that seem to be an arena for revenge and imprisonment. In the Islamic legal system, Allah SWT. Has prepared a number of legal instruments to regulate human life, specifically found in the Islamic banking system which has basic characters, namely zawajir (prevention) and zawabir (redeemer). There are two punishments given by Islam to criminals, namely Hudud (syar'i punishment) and Ta'zir (disciplinary sanction), prison in Islam can be found in Ta'zir sanctions. This refers to the notion of Ta'zir's punishment that the punishment for Jarimah (criminal act) whose punishment has not been determined by the syara 'is called ta'zir law. So that the general implementation guidelines for imprisonment as ta'zir, are left to the judge's ijtihad by taking into account the condition of the finger, the perpetrator, the place, the time, and the situation when the jarīmah occurs. This research uses literature research or library research. This means that the required data is taken from books, magazines, articles, papers and so on in accordance with the theme that the author will adopt with a juridical normative approach. This study also produces several findings, including that the history of the prison system process has undergone a metamorphosis from a prison system that focuses on deterrence to a system of rehabilitation and resocialization. That the implementation of the prison system in Indonesia is carried out with the correctional system and prisons in the Islamic law system are known as one of the punishments in the Ta'zir category. Besides also having a set of security rules that are guaranteed to realize rahmatan lil alamin if applied in social life.